Cardiometabolic Syndrome : An Emerging Global Health Issue - Patwary, Md Ismail; Talha, Khandaker Abu; Razzaque, Moona Farzana; Liza, Ferdousi Jannat; Istiaque, Ahmed (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Cardio metabolic syndrome (CMS) is a combination of metabolic dysfunctions characterized by insulin resistance, impaired glucose tolerance, dyslipidemia, hypertension and central obesity. CMS is recognized as a disease entity by the World Health Organization (WHO) and American Society of Endocrinology. CMS represents a constellation of metabolic abnormalities that are risk factors for cardiovascular diseases These cardiovascular and metabolic derangements individually and interdependently lead to increases in cerebrovascular disease(CVD) morbidity and mortality, making the CMS an established and strong risk factor for premature CVD. Data found that the prevalence of cardiometabolic syndrome (CMS) is increasing in all age groups, both in men and women from the latest National Health and Nutritional Examination Survey (NHANES).Alteration in fatty acid metabolism, such as excessive fatty acid release in the plasma is likely to contribute to these metabolic abnormalities. There is an established and proven benefits in reversing abnormal responses and decreasing cardiovascular risks by the treatment strategies including moderate physical activity, weight reduction, rigorous blood pressure control, correction of dyslipidemia and glycaemic control. J Bangladesh Coll Phys Surg 2022; 40: 287-291